2019
DOI: 10.3390/rs11121471
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Computation of the Volumes of Stockpiles of Bulk Material by Means of UAV Photogrammetric Surveying

Abstract: The monitoring and metric assessment of piles of natural or man-made materials plays a fundamental role in the production and management processes of multiple activities. Over time, the monitoring techniques have undergone an evolution linked to the progress of measure and data processing techniques; starting from classic topography to global navigation satellite system (GNSS) technologies up to the current survey systems like laser scanner and close-range photogrammetry. Last-generation 3D data management sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 28 publications
0
50
0
4
Order By: Relevance
“…Surface-volume ratio is one of the factors that taken into account in this study, the smaller the surface volume ratio, the more accurate the volume as shown in (table 2). This is also explained by (Tucci et al, 2019), as the surface-volume ratio decreases, the computed volume will be more accurate. The impact of flying height is also considered, the higher flight provides larger area coverage, but with larger value of ground sample distance GSD too.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Surface-volume ratio is one of the factors that taken into account in this study, the smaller the surface volume ratio, the more accurate the volume as shown in (table 2). This is also explained by (Tucci et al, 2019), as the surface-volume ratio decreases, the computed volume will be more accurate. The impact of flying height is also considered, the higher flight provides larger area coverage, but with larger value of ground sample distance GSD too.…”
Section: Discussionmentioning
confidence: 83%
“…There are four most frequently used methods for volume computation for different purposes which are : (Tucci et al, 2019) (Julge et al, 2019): 1. Cross sectional method.…”
Section: Methods Of Volume Computationmentioning
confidence: 99%
See 3 more Smart Citations